What We Gain by Combining Variationist and Concept‐Oriented Approaches: The Case of Acquiring Spanish Future‐Time Expression. Issue 2 (16th February 2017) - Kanwit, Matthew
Abstract: This study aimed to advance research on first and second language future‐time expression in Spanish and to demonstrate the strengths of combining functionalist, concept‐oriented approaches (e.g., Andersen, 1984; Bardovi‐Harlig, 2000; Shirai, 1995; von Stutterheim & Klein, 1987) with variationist approaches. The study targeted 140 participants (120 English‐speaking learners of Spanish of varying proficiency and 20 native speakers of Spanish) who completed an oral task responding to eight prompts (e.g., describe tus planes para este fin de semana "describe your plans for this weekend"). Results from cross‐tabulations and multinomial regressions indicated gradual inclusion of new linguistic and social variables as learner proficiency increased and demonstrated the value of considering both group and individual behavior. Findings were discussed in relation to stages of acquisition of future‐time expression. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .